2022
DOI: 10.1186/s12876-022-02253-6
|View full text |Cite
|
Sign up to set email alerts
|

Emphysematous cystitis as a potential marker of severe Crohn's disease

Abstract: Background Emphysematous cystitis (EC) is characterized by the presence of air within the bladder wall, often a complication of urinary tract infection (UTI) by gas-producing organisms. However, EC has also been reported in the setting of infectious colitis suggesting an alternate etiology. We report a rare case of EC in the setting of severe Crohn’s colitis with no clinical evidence of UTI. Case presentation A 43-year old female presented with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Cystitis (rank of APOP=3) is one of the top disease contexts identified by CONE. Clinical studies have shown that cystitis, an inflammation of the bladder, leads to a significant increase in the risk of IBD [5557]. For example, individuals with interstitial cystitis, a condition involving an inflamed or irritated bladder wall, are 100 times more likely to have IBD [57].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystitis (rank of APOP=3) is one of the top disease contexts identified by CONE. Clinical studies have shown that cystitis, an inflammation of the bladder, leads to a significant increase in the risk of IBD [5557]. For example, individuals with interstitial cystitis, a condition involving an inflamed or irritated bladder wall, are 100 times more likely to have IBD [57].…”
Section: Resultsmentioning
confidence: 99%
“…Cystitis (rank of APOP=3) is one of the top disease contexts identified by CONE. Clinical studies have shown that cystitis, an inflammation of the bladder, leads to a significant increase in the risk of IBD [55][56][57].…”
Section: Rq2mentioning
confidence: 99%